EFFECT OF MEDIAN ON LEVEL OF PERFORMANCE OF FOUR LANE ROAD IN BANDUNG - Tri Budiwati, Titik
EFFECT OF MEDIAN ON LEVEL OF PERFORMANCE OF FOUR-LANE ROAD IN BANDUNG, Titik Tri Budiwati, 1997, Program Sistem dan Teknik Jalan Raya, Program Pascasarjana, Institut Teknologi Bandung. Median may affect the capacity, free flow speed, traffic flow, overtaking maneuver etc. This thesis tries to study the effect of median on level of performance of four-lane road. The main objectives of the thesis are; to observe performance of urban road segments under given traffic flow and composition with median and without median, also to compare and identify the level of performance of road segment. Data- was collected from road segment, which had condition as below: • Four-Lane (4/2) urban_ road with and without_ median. • Flat terrain and straight-alignment. • Road width was approx. 12-15 meters and shoulder width 0-2- meters. The site location of- survey was chosen in link J1. Soekarno-Hatta between J1. Mohamad Toha-J1. Buah Batu intersection (undivided road- segment) and between J1. Buah Batu - Metro(divided road segment). The result of this study shows that speed for vehicle was used as dependent variable in the analysis. Speed-flow relationship- derived from speed-density relationship with slope - 0.4248 and -0.3476 for divided road and s-lope-. 1.5-166- and -1.3572 for undivided road (linea-r regress-ion) Free- flow speed in divided (45,90 km/h and 417,06 kin/h) is loWer- than in undivided (61.42 km/h and 5753 km/h)-, this- condition cause by unrecorded side friction -facto-r_ which wascounted from 100 m right and left sideof road -section,- any other reason were geometric- condition and tidffic priority whereas this situation could be disturbing the through traffic. Maximum flow and density in divided condition may be higher than in undivided road, it can be seen from figure speed-flow relationship and figure speed-density relationship.